Best of Both Worlds? Combining Physical and Mental Self-Management Strategies to Support Learning from Split-Attention Examples - Björn B. de Koning (MDPI AG, 2024)
The self-management principle holds that higher learning performance is obtained when learners actively use instructional strategies to manage the working memory load imposed by a learning task. Self-management studies with spatially separated but mutually referring text and pictures (split-attention examples) demonstrate the learning benefits of physical (e.g., annotation) and mental (imagined drag-and-drop) strategies. We investigated whether combining physical and mental strategies supports learning beyond a single strategy. Eighty-four participants studied a split-attention example with or without using a physical strategy and/or a mental strategy. Participants completed retention, comprehension, and transfer tests, and rated their cognitive load. Results showed that the combined use of physical and mental strategies resulted in lower cognitive load during learning than using the physical strategy and was more instructionally efficient compared to all other conditions. There were no significant differences regarding learning outcomes. Together, this suggests that combining physical and mental strategies is most supportive for studying split-attention examples.